Incidence, recurrence and management of electrical storm in Brugada syndrome - El-Battrawy, Ibrahim; Roterberg, Gretje; Kowitz, Jacqueline; Aweimer, Assem; Lang, Siegfried; Mügge, Andreas; Zhou, Xiao-Bo; Akın, Ibrahim (Frontiers in Cardiovascular Medicine, 2022)
Background: Brugada syndrome (BrS) is associated with ventricular tachyarrhythmias. However, the presence of electrical strom (ES) and its management still debated. Objectives: We present the outcome and management of 44 BrS patients suffering from ES. Methods: A systematic literature review and pooled analysis Through database review including PubMed, Web of Science, Cochrane Libary and Cinahl studies were analyzed. Evidence from 7 reports of 808 BrS patients was identified. Results: The mean age of patients suffering from ES was 34 ± 9.5 months (94.7% males, 65.8% spontaneous BrS type I). Using electrophysiological study ventricular tachycardia/ventricular fibrillation were inducible in 12/23 (52.2%). Recurrence of ES was documented in 6.1%. Death from ES was 8.2% after a follow-up of 83.5 ± 53.4. In up to 27 ES resolved without treatment. External shock was required in 35.6%, internal ICD shock in 13.3%, Overdrive pacing, left cardiac sympathetic block and atropin in 2.2%. Short-term antiarrhythmic management was as the following: Isopreterenol or Isopreterenol in combination with quinidine 35.5%, orciprenaline in 2.2%, quinidine 2.2%, disopyramide 2.2% or denopamide 2.2%. However, lidocaine, magensium sulfate, mexiletine and propanolol failed to control ES. Conclusion: Although ES is rare in BrS, this entity challenges physicians. Despite its high mortality rate, spontaneous termination is possible. Short-term management using Isoproterenol and/or quinidine might be safe. Prospective studies on management of ES are warranted.
Gesehen am 07.08.2023